Evaluation of traditional initial vancomycin dosing versus utilizing an electronic AUC/MIC dosing program - Kerri A. McGrady; Makenzie Benton; Serina Tart; Riley Bowers (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: Area under the curve to minimum inhibitory concentration (AUC/MIC) has been recommended by the 2020 updated vancomycin guidelines for dosing vancomycin for both efficacy and safety. Previously, AUC/MIC has been cumbersome to calculate so surrogate trough concentrations of 15-20 mg/dL were utilized. However, trough-based dosing is not a sufficient surrogate as AUC/MIC targets of 400-600 can usually be reached without achieving troughs of 15-20 mg/dL. Targeting higher trough levels may also lead to adverse events including acute kidney injury (AKI) and nephrotoxicity. Objective: To compare the mean total first day vancomycin dose in traditional trough-based dosing versus dosing recommended by an AUC/MIC dosing program. Methods: Adult inpatients who received at least 24 hours of IV vancomycin treatment were included in this single-center, retrospective cohort study. The primary endpoint was difference in mean total first day vancomycin dose in milligrams (mg) received between patients' traditional trough-based dosing and recommended dose via AUC/MIC electronic dosing calculator. Patients served as their own control by analyzing both actual dose received and dose recommended by the electronic AUC/MIC program. Rates of vancomycin induced adverse events, including acute kidney injury, elevated steady-state trough concentrations, and Red Man's syndrome were also compared between patients who received doses consistent with the AUC/MIC dosing recommendation versus those who did not. Results: 264 patients were included in this study. Initial 24-hour vancomycin exposure was significantly lower with the recommended AUC/MIC dose versus the dose received (2380.7; SD 966.6 mg vs 2649.6; SD 831.8 mg, [95% CI 114.7:423.1] p=0.0007). Conclusions: Utilizing an electronic AUC/MIC vancomycin dosing calculator would result in lower total first day vancomycin doses.